Konsep Keadilan dalam Filsafat Hukum: Analisis Perspektif Positivisme dan Hukum Alam - Lazarus L (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the classical debate between legal positivism and natural law theory in understanding the concept of justice. The tension between these two schools of thought has persisted for centuries and remains relevant in contemporary legal practice in Indonesia. Using a qualitative approach through library research, this study analyzes how each school defines justice, the implications for the formation of positive law, and their relevance to the Indonesian legal system. The findings indicate that legal positivism emphasizes legal certainty through the separation of law and morality, whereas natural law theory prioritizes the substantive notion of justice derived from universal values. In practice, the Indonesian legal system requires a synthesis of both perspectives to achieve substantive justice while ensuring legal certainty. This study recommends the adoption of an integrative approach that focuses not only on procedural aspects but also on the substantive dimensions of justice in every legal product.